NEW NATIONAL EDUCATION POLICY 2020 AND TRADITIONAL VALUES OF INDIAN EDUCATION - Mishra, Poonam; Yadav, Surmila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ancient Indian education was value-based, including the Gurukul system and the world-famous “Nalanda and Takshashila Universities”. Value-based education policy reforms were the basis for using knowledge for the benefit of mankind. Ancient India had knowledgeable personalities like Sushruta, Aryabhatta, Panini and Chanakya, who set examples before the world. The long-term impact in the national education system is the change from the 10+2 pattern to 5$3$3$3$4. This decision will bring a major change in the Indian education system after three decades. The new National Education Policy is promoting Indian value-based education with emphasis on holistic education, India-centric education, development of knowledge-based society, and knowledge-based education.